(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Centuries ago on this land of Vedas the teacher devoted on his time for the upliftment of his stupid in all direction knowledge moral and values at cetera she was called the Guru of Acharya. The real teacher characteristics on the laid down on the 13th chapter of the Bhagavad Gita are absence of pride, freedom from hypocrisy, non-violence, for giving nature, service of the preceptor, purity of mind and body, straightforwardness stead-fastness and self-control.